Influence of strain rate on the piezoresistive behavior of conductive polyamide composites - Zhang, M.; Chen, J.; Lu, Chunsheng (Elsevier, 2016)
© 2016 Elsevier Ltd. Due to the matrix viscosity, polyamide composites take on the obvious strain rate sensitivity that affects their conductivities during compression. In this paper, the influence of strain rate on the piezoresistive behavior of polyamide filled by stainless steel fibers and carbon nanotubes (SSFs/CNTs/PA6) is investigated. Based on experimental observations under compression, the resistivity of SSFs/CNTs/PA6 composites is dominated by two kinds of competing mechanisms: the spacing decrease between conductive fillers induced by compressive strain and the spacing increase due to micro-damage. A piezoresistivity model is proposed, which is coupled with the strain rate effect of SSFs/CNTs/PA6 composites. It is shown that there is a power-law relationship between the tunneling barrier and strain rate.